Surface anti-rust treatment agent for liquid storage tank of compressor and preparation method of surface anti-rust treatment agent

By preparing a compressor liquid storage tank surface anti-rust treatment agent containing a variety of active ingredients, the problem of rust on the surface of the liquid storage tank is solved, the density and durability of the anti-rust film are achieved, and the service life of the equipment is significantly extended.

CN119800367AActive Publication Date: 2025-04-11HEFEI LUTUO NEW MATERIAL TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510277857.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-11
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

The surface of the liquid storage tank is prone to rust, resulting in a degradation of the equipment's performance and the existing anti-rust treatment agent is not lasting.

Method used

A compressor liquid reservoir surface anti-rust treatment agent is adopted, and its raw materials include alkaline corrosion inhibitor, glycerol, isomer alcohol carboxylate, inorganic alkali, terminal amino polyamide-amine, dopamine, pretreated montmorillonite, saturated ammonia water, branched isomer alcohol ether, isooctyl glucoside, penetrant, dispersant, chelating agent and water. It is prepared by sonication and stirring, forming a dense anti-rust film.

Benefits of technology

It significantly extends the anti-rust time on the surface of the liquid storage tank, improves the stability and adhesion of the anti-rust film, effectively blocks corrosive media such as moisture and air, and significantly enhances the rust removal and rust prevention ability of the workpiece.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800367A_ABST
    Figure CN119800367A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of surface anti-rust treatment, in particular to a compressor liquid storage tank surface anti-rust treatment agent and a preparation method thereof. The surface anti-rust treatment agent for the liquid storage tank of the compressor comprises the following raw materials in parts by mass: 0.1-1 part of an alkaline corrosion inhibitor, 0.1-1 part of glycerol, 1-5 parts of isomeric alcohol carboxylate, 1-3 parts of inorganic alkali, 1-3 parts of amino-terminated polyamide-amine, 1-3 parts of dopamine, 5-10 parts of pretreated montmorillonite, 1-5 parts of saturated ammonia water, 5-15 parts of branched isomeric alcohol ether and 1-2 parts of isooctyl glucoside. 1-5 parts of a penetrating agent, 1-5 parts of a dispersing agent, 1-5 parts of a chelating agent and 60-100 parts of water. The steel corrosion inhibitor has no obvious visible corrosion to steel, has the advantages of high acting speed, stable property and no toxic effect on human bodies, is simple in preparation method, is suitable for large-scale popularization and application, and has very high practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface antirust treatment, and in particular to a surface antirust treatment agent for a compressor liquid storage tank and a preparation method thereof. Background Art

[0002] As an important component in the air-conditioning system, the liquid storage tank is suitable for the suction end of the compressor. Its function is to inhale the refrigerant through the air-conditioning refrigeration cycle, filter it and transport it to the compression chamber of the compressor for the next round of refrigeration cycle.

[0003] The processed surface of the workpiece of the liquid storage tank may rust, and the workpiece surface needs to be treated with rust prevention. At the same time, the liquid storage tank is very easy to come into contact with oxygen, moisture or other corrosive media in the air. As time goes by, electrochemical corrosion will easily occur on the mechanical metal surface and rust, which may greatly affect the performance of the equipment.

[0004] At present, the commonly used method is to use rust inhibitors to treat the workpiece surface to protect the metal from rusting before use. It can also play a certain protective role on the metal surface to prevent minor scratches and has a good short-term anti-rust effect. The anti-rust time is generally not long after treatment.

[0005] Therefore, it is an urgent problem to provide an anti-rust treatment agent for a liquid storage tank to effectively prevent surface rust, increase its service life and increase its stability. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a surface rust-proof treatment agent for a compressor liquid storage tank and a preparation method thereof.

[0007] A rust-proof treatment agent for the surface of a compressor liquid storage tank, the raw materials of which include, by mass, 0.1-1 part of an alkaline corrosion inhibitor, 0.1-1 part of propylene glycol, 1-5 parts of isomeric alcohol carboxylates, 1-3 parts of an inorganic base, 1-3 parts of amino-terminated polyamide-amine, 1-3 parts of dopamine, 5-10 parts of pretreated montmorillonite, 1-5 parts of saturated ammonia water, 5-15 parts of branched isomeric alcohol ethers, 1-2 parts of isooctyl glucoside, 1-5 parts of a penetrant, 1-5 parts of a dispersant, 1-5 parts of a chelating agent, and 60-100 parts of water.

[0008] Preferably, the inorganic base is at least one of sodium hydroxide, potassium hydroxide, barium hydroxide, calcium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate and potassium bicarbonate.

[0009] Preferably, the alkaline corrosion inhibitor is compounded from a polymerized potassium inorganic compound, does not contain phosphorus and nitrogen elements, has high environmental protection requirements, and is miscible with most commonly used inorganic alkali salts without rejection.

[0010] Preferably, the branched isomeric alcohol ether is fatty alcohol polyoxyethylene ether.

[0011] Preferably, the generation number of the amino-terminated polyamidoamine is 2.0-4.0 generations.

[0012] Preferably, the penetrant is at least one of JFC-M, JFC-S and JFC-E.

[0013] Preferably, the dispersant is an organic acid salt dispersant or / and an alkylnaphthalene sulfonate. Preferably, the alkylnaphthalene sulfonate is sodium dodecylnaphthalene sulfonate (CAS: 40382-75-0) or the like.

[0014] Preferably, the dispersant is composed of octa-isomeric carboxylic acid salt (ie, sodium isooctanoate) and alkylnaphthalene sulfonate.

[0015] Preferably, the chelating agent is at least one of sodium polyepoxysuccinate, tetrasodium glutamate diacetate, and trisodium methylglycine diacetate; preferably, it is a combination of sodium polyepoxysuccinate and trisodium methylglycine diacetate.

[0016] Preferably, the pretreated montmorillonite is prepared by the following steps: adding nano-montmorillonite and nano-molybdenum oxide to isopropanol for ultrasonic treatment for 2-4 hours, adding saturated ammonia water, stirring at 80-90°C for 1-2 hours, filtering, washing, and vacuum drying; adding to water, adding zinc acetate thereto, stirring at 50-70°C for 1-2 hours, adding ammonia water with a mass fraction of 8-10% thereto under stirring, continuing to stir for 1-2 hours, filtering, washing, roasting at 300-400°C for 1-2 hours, cooling to room temperature, and crushing.

[0017] The present invention peels off the nano-montmorillonite sheet structure, promotes the intercalation of nano-molybdenum oxide therein, further activates the sheet structure with amino groups, and the nano-zinc oxide is attached and combined with the sheet surface with extremely high stability. The molybdenum atoms thereon can be efficiently and stably combined with the surface of the liquid storage tank, which can achieve rust removal and rust prevention effects while facilitating the further progress of subsequent processes.

[0018] More preferably, the particle size of the nano-molybdenum oxide is 50-200 nm.

[0019] More preferably, the mass ratio of nano-montmorillonite, nano-molybdenum oxide and zinc acetate is 5-10:1-2:1-2.

[0020] The preparation method of the above compressor liquid storage tank surface rust preventive treatment agent comprises the following steps: S1. Add inorganic alkali to water, stir evenly at 20-30°C, add alkaline corrosion inhibitor, glycerol, isomeric alcohol carboxylate and stir evenly to obtain prefabricated material. a ; S2. Add branched isomeric alcohol ether, isooctyl glucoside, penetrant, dispersant, chelating agent, and amino-terminated polyamide-amine to water, and stir at 30-40° C. for 1-2 hours to obtain a prefabricated material. b ; S3, add dopamine to water, add pretreated montmorillonite, add saturated ammonia water, stir at 40-60℃ for 1-2h, centrifuge, wash, and vacuum dry; add prefabricated material a and prefabricated materials b Ultrasonic treatment for 10-30 min.

[0021] The method for using the above-mentioned compressor liquid storage tank surface rust prevention agent comprises the following steps: using the above-mentioned compressor liquid storage tank surface rust prevention agent to vertically spray the compressor liquid storage tank after the leak detection and water inspection.

[0022] Beneficial effects: The present invention deposits a polydopamine layer on the pretreated montmorillonite, which not only improves the hydrophilicity of the montmorillonite, enhances the interface effect between the montmorillonite and the substrate, has excellent dispersibility and interface compatibility, and further improves its anti-rust performance, but also nano-molybdenum oxide and nano-zinc oxide combined with the surface of the pretreated montmorillonite cooperate with the polydopamine deposited on the surface to form a dense film on the surface of the workpiece. The dense and compact anti-rust film can effectively block the entry of corrosive media such as moisture and air, greatly prolong the anti-rust time, and has excellent stability performance.

[0023] The present invention combines polydopamine on the surface of pretreated montmorillonite. The surface of the pretreated montmorillonite has a large number of active amino groups and cooperates with the amino-terminated polyamide-amine. The two have extremely high affinity, which can not only effectively increase the stability of the system, but also significantly enhance the binding force of the rust-proof treatment agent on the steel material. A stable protective film can be formed on the substrate to prevent oxidation and prevent rust on the surface of the workpiece. It has excellent durability and adhesion performance, strong rust removal and rust prevention capabilities for the workpiece, and greatly extends the rust prevention time.

[0024] The invention has no obvious visible corrosion to steel, and at the same time has a fast action speed, stable properties, no toxicity to human body, simple preparation method, suitable for large-scale promotion and application, and has high practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The Tafel polarization curves are obtained after spraying Q235 carbon steel plates with the anti-rust treatment agent obtained in Example 5 and Comparative Examples 1-3.

[0026] Figure 2 This is a comparison chart of corrosion potential and corrosion current density after spraying Q235 carbon steel plates with the anti-rust treatment agents obtained in Example 5 and Comparative Examples 1-3.

[0027] Figure 3This is a comparison chart of the corrosion rates of Q235 carbon steel plates after spraying the anti-rust treatment agents obtained in Example 5 and Comparative Examples 1-3. DETAILED DESCRIPTION

[0028] The present invention will be further explained below in conjunction with specific embodiments.

[0029] Isomeric alcohol carboxylates are an organic compound of alkyl carboxylic acid isomeric branched alcohol amine soaps, synthesized from polycarboxylic acids and isomeric organic amines, and were purchased from Xu New Materials (Guangzhou) Co., Ltd. Alkaline corrosion inhibitors were purchased from Guangdong Jiemu Chemical Co., Ltd., model W-10A. Penetrant JFC-S was purchased from Nantong Run Chemical Co., Ltd., and its type is non-ionic surfactant, and its chemical composition is polyoxyethylene ether compound.

[0030] Example 1 A rust-proof treatment agent for the surface of a compressor liquid storage tank, the raw materials of which include: 1g of alkaline corrosion inhibitor, 1g of glycerol, 10g of isomeric alcohol carboxylate DX-S202, 10g of potassium hydroxide, 10g of 2.0-generation amino-terminated polyamide-amine, 10g of dopamine, 50g of pretreated montmorillonite, 10g of saturated ammonia water, 50g of fatty alcohol polyoxyethylene ether, 10g of isooctyl glucoside, 10g of penetrant JFC-S, 10g of dispersant, 10g of chelating agent, and 600g of water.

[0031] The dispersant is composed of sodium isooctanoate and alkylnaphthalene sulfonate in a mass ratio of 1:1. The chelating agent is composed of sodium polyepoxysuccinate and trisodium methylglycine diacetate in a mass ratio of 1:1.

[0032] The pretreated montmorillonite was prepared by the following steps: 50 g of nano-montmorillonite and 10 g of nano-molybdenum oxide with an average particle size of 80 nm were added to 200 g of isopropanol, ultrasonically treated at a frequency of 5 kHz for 2 h, 10 g of saturated ammonia water was added, stirred at a temperature of 80°C for 1 h, filtered, washed, and vacuum dried; added to 1000 g of water, 10 g of zinc acetate was added thereto, stirred at a temperature of 50°C for 1 h, 10 g of ammonia water with a mass fraction of 8% was added thereto under stirring, stirring was continued for 1 h, filtered, washed, roasted at a temperature of 300°C for 1 h, cooled to room temperature, and crushed.

[0033] The preparation method of the above compressor liquid storage tank surface rust preventive treatment agent comprises the following steps: S1. Add potassium hydroxide to 200g water, stir evenly at a temperature of 20°C, add alkaline corrosion inhibitor, glycerol, and isomeric alcohol carboxylate DX-S202 in sequence and stir evenly to obtain a prefabricated material. a ; S2. Add fatty alcohol polyoxyethylene ether, isooctyl glucoside, penetrant JFC-S, dispersant, chelating agent, and amino-terminated polyamide-amine to 400 g of water and stir at 30° C. for 1 h to obtain a prefabricated material. b ; S3, add dopamine to 200g water, add pretreated montmorillonite, add saturated ammonia water, stir at 40°C for 1h, centrifuge, wash with ethanol, and vacuum dry; add prefabricated material a and prefabricated materials b Ultrasonic treatment was performed for 10 min at a frequency of 4 kHz.

[0034] Example 2 A rust-proof treatment agent for the surface of a compressor liquid storage tank, the raw materials of which include: 10g of alkaline corrosion inhibitor, 10g of glycerol, 50g of isomeric alcohol carboxylate DX-S202, 30g of potassium hydroxide, 30g of 4.0-generation amino-terminated polyamide-amine, 30g of dopamine, 100g of pretreated montmorillonite, 50g of saturated ammonia water, 150g of fatty alcohol polyoxyethylene ether, 20g of isooctyl glucoside, 50g of penetrant JFC-S, 50g of dispersant, 50g of chelating agent and 1000g of water.

[0035] The dispersant is composed of sodium isooctanoate and alkylnaphthalene sulfonate in a mass ratio of 1:1. The chelating agent is composed of sodium polyepoxysuccinate and trisodium methylglycine diacetate in a mass ratio of 3:1.

[0036] The pretreated montmorillonite was prepared by the following steps: 100 g of nano-montmorillonite and 20 g of nano-molybdenum oxide with an average particle size of 150 nm were added to 400 g of isopropanol, ultrasonically treated at a frequency of 10 kHz for 4 h, 100 g of saturated ammonia water was added, stirred at a temperature of 90°C for 2 h, filtered, washed, and vacuum dried; added to 2000 g of water, 20 g of zinc acetate was added thereto, stirred at a temperature of 70°C for 2 h, 50 g of ammonia water with a mass fraction of 10% was added thereto under stirring, stirring was continued for 2 h, filtered, washed, roasted at a temperature of 400°C for 2 h, cooled to room temperature, and crushed.

[0037] The preparation method of the above compressor liquid storage tank surface rust preventive treatment agent comprises the following steps: S1. Add potassium hydroxide to 500g water, stir evenly at a temperature of 30°C, add alkaline corrosion inhibitor, glycerol, and isomeric alcohol carboxylate DX-S202 in sequence and stir evenly to obtain a prefabricated material. a ; S2. Add fatty alcohol polyoxyethylene ether, isooctyl glucoside, penetrant JFC-S, dispersant, chelating agent, and amino-terminated polyamide-amine to 500 g of water and stir at 40° C. for 2 h to obtain a prefabricated material. b ; S3, add dopamine to 500g water, add pretreated montmorillonite, add saturated ammonia water, stir at 60°C for 2h, centrifuge, wash with ethanol, and vacuum dry; add prefabricated material a and prefabricated materials b Ultrasonic treatment was performed for 30 min at a frequency of 10 kHz.

[0038] Example 3 A surface rust preventive treatment agent for a compressor liquid storage tank, the raw materials of which include: 7g of alkaline corrosion inhibitor, 2g of glycerol, 40g of isomeric alcohol carboxylate DX319, 15g of potassium hydroxide, 15g of 3.5-generation amino-terminated polyamide-amine, 25g of dopamine, 70g of pretreated montmorillonite, 40g of saturated ammonia water, 80g of fatty alcohol polyoxyethylene ether, 17g of isooctyl glucoside, 20g of penetrant JFC-S, 40g of dispersant, 20g of chelating agent and 720g of water.

[0039] The dispersant is composed of sodium isooctanoate and alkylnaphthalene sulfonate in a mass ratio of 2:1. The chelating agent is composed of sodium polyepoxysuccinate and trisodium methylglycine diacetate in a mass ratio of 1:4.

[0040] The pretreated montmorillonite was prepared by the following steps: 90 g of nano-montmorillonite and 12 g of nano-molybdenum oxide with an average particle size of 100 nm were added to 350 g of isopropanol, ultrasonically treated at a frequency of 6 kHz for 3.5 h, 20 g of saturated ammonia water was added, stirred at a temperature of 88°C for 80 min, filtered, washed, and vacuum dried; added to 1800 g of water, 13 g of zinc acetate was added thereto, stirred at a temperature of 65°C for 80 min, 40 g of ammonia water with a mass fraction of 8.5% was added thereto under stirring, stirring was continued for 100 min, filtered, washed, roasted at a temperature of 330°C for 100 min, cooled to room temperature, and crushed.

[0041] The preparation method of the above compressor liquid storage tank surface rust preventive treatment agent comprises the following steps: S1. Add potassium hydroxide to 300g water, stir evenly at a temperature of 28°C, add alkaline corrosion inhibitor, glycerol, and isomeric alcohol carboxylate DX319 in sequence and stir evenly to obtain a prefabricated material. a ; S2, add fatty alcohol polyoxyethylene ether, isooctyl glucoside, penetrant JFC-S, dispersant, chelating agent, amino-terminated polyamide-amine to 420g water, stir at 37°C for 80min, and obtain a prefabricated material. b ; S3, add dopamine to 400g water, add pretreated montmorillonite, add saturated ammonia water, stir at 55°C for 80min, centrifuge, wash with ethanol, and vacuum dry; add prefabricated material a and prefabricated materials bUltrasonic treatment was performed for 25 min at a frequency of 6 kHz.

[0042] Example 4 A surface rust preventive treatment agent for a compressor liquid storage tank, the raw materials of which include: 3g of alkaline corrosion inhibitor, 8g of glycerol, 20g of isomeric alcohol carboxylate DX319, 25g of potassium hydroxide, 25g of 2.5-generation amino-terminated polyamide-amine, 15g of dopamine, 90g of pretreated montmorillonite, 20g of saturated ammonia water, 120g of fatty alcohol polyoxyethylene ether, 13g of isooctyl glucoside, 40g of penetrant JFC-S, 20g of dispersant, 40g of chelating agent and 880g of water.

[0043] The dispersant is composed of sodium isooctanoate and alkylnaphthalene sulfonate in a mass ratio of 1:3. The chelating agent is composed of sodium polyepoxysuccinate and trisodium methylglycine diacetate in a mass ratio of 2:1.

[0044] The pretreated montmorillonite was prepared by the following steps: 70 g of nano-montmorillonite and 18 g of nano-molybdenum oxide with an average particle size of 100 nm were added to 200 g of isopropanol, ultrasonically treated at a frequency of 9 kHz for 2.5 h, 80 g of saturated ammonia water was added, stirred at a temperature of 82°C for 100 min, filtered, washed, and vacuum dried; added to 1200 g of water, 17 g of zinc acetate was added thereto, stirred at a temperature of 55°C for 100 min, 20 g of ammonia water with a mass fraction of 9.5% was added thereto under stirring, stirring was continued for 80 min, filtered, washed, roasted at a temperature of 370°C for 80 min, cooled to room temperature, and crushed.

[0045] The preparation method of the above compressor liquid storage tank surface rust preventive treatment agent comprises the following steps: S1. Add potassium hydroxide to 400g water, stir evenly at a temperature of 22°C, add alkaline corrosion inhibitor, glycerol, and isomeric alcohol carboxylate DX319 in sequence and stir evenly to obtain a prefabricated material. a ; S2, add fatty alcohol polyoxyethylene ether, isooctyl glucoside, penetrant JFC-S, dispersant, chelating agent, amino-terminated polyamide-amine to 480g water, stir at 33°C for 100min, and obtain a prefabricated material. b ; S3, add dopamine to 300g water, add pretreated montmorillonite, add saturated ammonia water, stir at 45°C for 100min, centrifuge, wash with ethanol, and vacuum dry; add prefabricated material a and prefabricated materials b Ultrasonic treatment was performed for 15 min at a frequency of 9 kHz.

[0046] Example 5 A surface rust preventive treatment agent for a compressor liquid storage tank, the raw materials of which include: 5g of alkaline corrosion inhibitor, 5g of glycerol, 30g of isomeric alcohol carboxylate DX320, 20g of potassium hydroxide, 20g of 3.0-generation amino-terminated polyamide-amine, 20g of dopamine, 80g of pretreated montmorillonite, 30g of saturated ammonia water, 100g of fatty alcohol polyoxyethylene ether, 15g of isooctyl glucoside, 30g of penetrant JFC-S, 30g of dispersant, 30g of chelating agent and 800g of water.

[0047] The dispersant is composed of sodium isooctanoate and alkylnaphthalene sulfonate in a mass ratio of 1:1. The chelating agent is composed of sodium polyepoxysuccinate and trisodium methylglycine diacetate in a mass ratio of 1:1.

[0048] The pretreated montmorillonite was prepared by the following steps: 80g of nano-montmorillonite and 15g of nano-molybdenum oxide with an average particle size of 100nm were added to 300g of isopropanol, ultrasonically treated at a frequency of 7.5kHz for 3h, 50g of saturated ammonia water was added, stirred at a temperature of 85°C for 90min, filtered, washed, and vacuum dried; added to 1500g of water, 15g of zinc acetate was added thereto, stirred at a temperature of 60°C for 90min, 30g of ammonia water with a mass fraction of 9% was added thereto under stirring, stirring was continued for 90min, filtered, washed, roasted at a temperature of 350°C for 90min, cooled to room temperature, and crushed.

[0049] The preparation method of the above compressor liquid storage tank surface rust preventive treatment agent comprises the following steps: S1. Add potassium hydroxide to 350g water, stir evenly at a temperature of 25°C, add alkaline corrosion inhibitor, glycerol, and isomeric alcohol carboxylate DX320 in sequence and stir evenly to obtain a prefabricated material. a ; S2, add fatty alcohol polyoxyethylene ether, isooctyl glucoside, penetrant JFC-S, dispersant, chelating agent, amino-terminated polyamide-amine to 450g water, stir at 35°C for 90min, and obtain a prefabricated material. b ; S3, add dopamine to 350g water, add pretreated montmorillonite, add saturated ammonia water, stir at 50°C for 90min, centrifuge, wash with ethanol, and vacuum dry; add prefabricated material a and prefabricated materials b Ultrasonic treatment was performed for 20 min at a frequency of 7.5 kHz.

[0050] Comparative Example 1 A compressor liquid storage tank surface rust prevention treatment agent, the raw materials of which include: 5g of alkaline corrosion inhibitor, 5g of glycerol, 30g of isomeric alcohol carboxylate DX320, 20g of potassium hydroxide, 20g of dopamine, 80g of pretreated montmorillonite, 30g of saturated ammonia water, 100g of fatty alcohol polyoxyethylene ether, 15g of isooctyl glucoside, 30g of penetrant JFC-S, 30g of dispersant, 30g of chelating agent, and 820g of water.

[0051] The dispersant is composed of sodium isooctanoate and alkylnaphthalene sulfonate in a mass ratio of 1:1. The chelating agent is composed of sodium polyepoxysuccinate and trisodium methylglycine diacetate in a mass ratio of 1:1.

[0052] The pretreated montmorillonite was prepared by the following steps: 80g of nano-montmorillonite and 15g of nano-molybdenum oxide with an average particle size of 100nm were added to 300g of isopropanol, ultrasonically treated at a frequency of 7.5kHz for 3h, 50g of saturated ammonia water was added, stirred at a temperature of 85°C for 90min, filtered, washed, and vacuum dried; added to 1500g of water, 15g of zinc acetate was added thereto, stirred at a temperature of 60°C for 90min, 30g of ammonia water with a mass fraction of 9% was added thereto under stirring, stirring was continued for 90min, filtered, washed, roasted at a temperature of 350°C for 90min, cooled to room temperature, and crushed.

[0053] The preparation method of the above compressor liquid storage tank surface rust preventive treatment agent comprises the following steps: S1. Add potassium hydroxide to 350g water, stir evenly at a temperature of 25°C, add alkaline corrosion inhibitor, glycerol, and isomeric alcohol carboxylate DX320 in sequence and stir evenly to obtain a prefabricated material. a ; S2. Add fatty alcohol polyoxyethylene ether, isooctyl glucoside, penetrant JFC-S, dispersant, and chelating agent to 470 g of water, and stir at 35° C. for 90 min to obtain a prefabricated material. b ; S3, add dopamine to 350g water, add pretreated montmorillonite, add saturated ammonia water, stir at 50°C for 90min, centrifuge, wash with ethanol, and vacuum dry; add prefabricated material a and prefabricated materials b Ultrasonic treatment was performed for 20 min at a frequency of 7.5 kHz.

[0054] Comparative Example 2 A surface rust preventive treatment agent for a compressor liquid storage tank, the raw materials of which include: 5g of alkaline corrosion inhibitor, 5g of glycerol, 30g of isomeric alcohol carboxylate DX320, 20g of potassium hydroxide, 20g of 3.0-generation amino-terminated polyamide-amine, 80g of pretreated montmorillonite, 100g of fatty alcohol polyoxyethylene ether, 15g of isooctyl glucoside, 30g of penetrant JFC-S, 30g of dispersant, 30g of chelating agent and 850g of water.

[0055] The dispersant is composed of sodium isooctanoate and alkylnaphthalene sulfonate in a mass ratio of 1:1. The chelating agent is composed of sodium polyepoxysuccinate and trisodium methylglycine diacetate in a mass ratio of 1:1.

[0056] The pretreated montmorillonite was prepared by the following steps: 80g of nano-montmorillonite and 15g of nano-molybdenum oxide with an average particle size of 100nm were added to 300g of isopropanol, ultrasonically treated at a frequency of 7.5kHz for 3h, 50g of saturated ammonia water was added, stirred at a temperature of 85°C for 90min, filtered, washed, and vacuum dried; added to 1500g of water, 15g of zinc acetate was added thereto, stirred at a temperature of 60°C for 90min, 30g of ammonia water with a mass fraction of 9% was added thereto under stirring, stirring was continued for 90min, filtered, washed, roasted at a temperature of 350°C for 90min, cooled to room temperature, and crushed.

[0057] The preparation method of the above compressor liquid storage tank surface rust preventive treatment agent comprises the following steps: S1. Add potassium hydroxide to 350g water, stir evenly at a temperature of 25°C, add alkaline corrosion inhibitor, glycerol, and isomeric alcohol carboxylate DX320 in sequence and stir evenly to obtain a prefabricated material. a ; S2. Add fatty alcohol polyoxyethylene ether, isooctyl glucoside, penetrant JFC-S, dispersant, chelating agent, and amino-terminated polyamide-amine to 500 g of water, and stir at 35° C. for 90 min to obtain a prefabricated material. b ; S3. Adding prefabricated material to pretreated montmorillonite a and prefabricated materials b Ultrasonic treatment was performed for 20 min at a frequency of 7.5 kHz.

[0058] Comparative Example 3 A surface rust preventive treatment agent for a compressor liquid storage tank, the raw materials of which include: 5g of alkaline corrosion inhibitor, 5g of glycerol, 30g of isomeric alcohol carboxylate DX320, 20g of potassium hydroxide, 20g of 3.0-generation amino-terminated polyamide-amine, 20g of dopamine, 80g of pretreated montmorillonite, 30g of saturated ammonia water, 100g of fatty alcohol polyoxyethylene ether, 15g of isooctyl glucoside, 30g of penetrant JFC-S, 30g of dispersant, 30g of chelating agent and 800g of water.

[0059] The dispersant is composed of sodium isooctanoate and alkylnaphthalene sulfonate in a mass ratio of 1:1. The chelating agent is composed of sodium polyepoxysuccinate and trisodium methylglycine diacetate in a mass ratio of 1:1.

[0060] The pretreated montmorillonite was prepared by the following steps: 80 g of nano-montmorillonite and 15 g of nano-molybdenum oxide with an average particle size of 100 nm were added to 1500 g of water, 15 g of zinc acetate was added thereto, and the mixture was stirred at 60° C. for 90 min. 30 g of 9% ammonia water was added thereto under stirring, and the mixture was stirred for 90 min. The mixture was filtered, washed, calcined at 350° C. for 90 min, cooled to room temperature, and crushed.

[0061] The preparation method of the above compressor liquid storage tank surface rust preventive treatment agent comprises the following steps: S1. Add potassium hydroxide to 350g water, stir evenly at a temperature of 25°C, add alkaline corrosion inhibitor, glycerol, and isomeric alcohol carboxylate DX320 in sequence and stir evenly to obtain a prefabricated material. a ; S2, add fatty alcohol polyoxyethylene ether, isooctyl glucoside, penetrant JFC-S, dispersant, chelating agent, amino-terminated polyamide-amine to 450g water, stir at 35°C for 90min, and obtain a prefabricated material. b ; S3, add dopamine to 350g water, add pretreated montmorillonite, add saturated ammonia water, stir at 50°C for 90min, centrifuge, wash with ethanol, and vacuum dry; add prefabricated material a and prefabricated materials b Ultrasonic treatment was performed for 20 min at a frequency of 7.5 kHz.

[0062] The rust-proof treatment agents obtained in Example 5 and Comparative Examples 1-3 were subjected to stability tests, as follows: (1) High temperature experiment: Place 50 mL of each group of anti-rust treatment agent in a measuring cylinder, seal it, and place it in a constant temperature water bath at 60±2℃, making sure that the water surface is above 2 / 3 of the measuring cylinder. After the experimental period (72 hours), take out the measuring cylinder, cool it to room temperature, and then check it.

[0063] Each group of anti-rust treatment agents remained uniform without stratification or precipitation.

[0064] (2) Low temperature experiment: Place 50 mL of each group of anti-rust treatment agent in a measuring cylinder, seal it, and place it in an environment of -5±2℃. After the experimental period (72h), take out the measuring cylinder and return it to room temperature before inspection.

[0065] Each group of anti-rust treatment agents remained uniform, and no stratification or precipitation occurred.

[0066] A Q235 carbon steel plate (specification: 80mm×40mm×3mm) was used, and then the surface rust and oil were removed, and the steel sample was obtained after sandpaper polishing and cleaning. The anti-rust treatment agent obtained in Example 5 and Comparative Examples 1-3 was sprayed on the surface of the steel sample, and dried naturally. Then, paraffin wax and rosin mixed in a ratio of 1:1 were used for sealing, leaving only a working area (10mm×10mm).

[0067] The Tafel polarization curves of the steel samples after each group of anti-rust treatment were tested using an electrochemical workstation. The corrosive medium was a 3% sodium chloride aqueous solution, a platinum electrode was used as the auxiliary electrode, a saturated calomel electrode was used as the reference electrode, and the steel samples after each group of anti-rust treatment were used as the working electrode.

[0068] The test parameters are as follows: initial potential is -1.20 V, termination potential is -0.00 V, scanning speed is 0.005 V / s, waiting time is 0 s, current polarization mode is reduction, and frequency is 50 Hz.

[0069] The results are as follows Figure 1 and Figure 2 As shown, the steel sample sprayed with the anti-rust treatment agent obtained in Example 5 has the largest corrosion resistance potential and the smallest corrosion current density, which is better than that of Comparative Examples 1-3 (P < 0.05).

[0070] The corrosion current density value obtained from the Tafel polarization curve can be used to calculate the corrosion rate of the sample steel after being treated with the rust preventive agent, such as Figure 3 As shown, the corrosion rate of the steel sample sprayed with the anti-rust treatment agent obtained in Example 5 is the smallest, which is better than that of Comparative Examples 1-3 (P < 0.05).

[0071] The applicant believes that this is because: the present invention deposits a polydopamine layer on the pretreated montmorillonite, which not only improves the hydrophilicity of the montmorillonite, improves the interface between it and the substrate, has excellent dispersibility and interface compatibility, and further improves its anti-rust performance, and the nano-molybdenum oxide and nano-zinc oxide combined on the surface of the pretreated montmorillonite, cooperate with the surface deposited polydopamine, form a dense film on the surface of the workpiece, the anti-rust film is dense and compact, can effectively block the entry of corrosive media such as moisture and air, greatly prolong the anti-rust time, and has excellent stability. The present invention combines polydopamine on the surface of the pretreated montmorillonite, the surface of the pretreated montmorillonite has a large number of active amino groups, and cooperates with the amino-terminated polyamide-amine, the two have extremely high affinity, can not only effectively increase the stability of the system, but also can significantly enhance the binding force of the anti-rust treatment agent on the steel material, can form a layer of stable protective film on the substrate to prevent oxidation, further prevent the workpiece processing surface from rusting, and has excellent durability and adhesion performance, which not only makes the workpiece strong in rust removal and rust prevention, but also greatly prolongs the anti-rust time.

[0072] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A rust-proof treatment agent for the surface of a compressor liquid storage tank, characterized in that: The raw materials include, by mass, 0.1-1 parts of alkaline corrosion inhibitor, 0.1-1 parts of propylene glycol, 1-5 parts of isomeric alcohol carboxylates, 1-3 parts of inorganic bases, 1-3 parts of amino-terminated polyamide-amines, 1-3 parts of dopamine, 5-10 parts of pretreated montmorillonite, 1-5 parts of saturated ammonia water, 5-15 parts of branched isomeric alcohol ethers, 1-2 parts of isooctyl glucoside, 1-5 parts of penetrants, 1-5 parts of dispersants, 1-5 parts of chelating agents, and 60-100 parts of water.

2. The anti-rust treatment agent for the surface of the compressor liquid storage tank according to claim 1, characterized in that: The inorganic base is at least one of sodium hydroxide, potassium hydroxide, barium hydroxide, calcium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate and potassium bicarbonate.

3. The anti-rust treatment agent for the surface of the compressor liquid storage tank according to claim 1, characterized in that: Branched isomeric alcohol ethers are fatty alcohol polyoxyethylene ethers.

4. The anti-rust treatment agent for the surface of the compressor liquid storage tank according to claim 1, characterized in that: The dispersant is an organic acid salt dispersant and / or an alkylnaphthalene sulfonate.

5. The anti-rust treatment agent for the surface of the compressor liquid storage tank according to claim 1, characterized in that: The chelating agent is at least one of sodium polyepoxysuccinate, tetrasodium glutamate diacetate, and trisodium methylglycine diacetate.

6. The anti-rust treatment agent for the surface of the compressor liquid storage tank according to claim 1, characterized in that: The pretreated montmorillonite is prepared by the following steps: adding nano-montmorillonite and nano-molybdenum oxide to isopropanol for ultrasonic treatment for 2-4 hours, adding saturated ammonia water, stirring at 80-90°C for 1-2 hours, filtering, washing, and vacuum drying; adding to water, adding zinc acetate thereto, stirring at 50-70°C for 1-2 hours, adding ammonia water with a mass fraction of 8-10% thereto under stirring, continuing to stir for 1-2 hours, filtering, washing, roasting at 300-400°C for 1-2 hours, cooling to room temperature, and crushing.

7. The anti-rust treatment agent for the surface of the compressor liquid storage tank according to claim 6, characterized in that: The mass ratio of nano-montmorillonite, nano-molybdenum oxide and zinc acetate is 5-10:1-2:1-2.

8. A method for preparing the anti-rust treatment agent for the surface of a compressor liquid storage tank according to any one of claims 1 to 7, characterized in that: The steps include: S1. Add inorganic alkali to water, stir evenly at 20-30°C, add alkaline corrosion inhibitor, glycerol, isomeric alcohol carboxylate and stir evenly to obtain prefabricated material. a ; S2. Add branched isomeric alcohol ether, isooctyl glucoside, penetrant, dispersant, chelating agent, and amino-terminated polyamide-amine to water, and stir at 30-40° C. for 1-2 hours to obtain a prefabricated material. b ; S3, add dopamine to water, add pretreated montmorillonite, add saturated ammonia water, stir at 40-60℃ for 1-2h, centrifuge, wash, and vacuum dry; add prefabricated material a and prefabricated materials b Ultrasonic treatment for 10-30 min.

9. A method for using the anti-rust treatment agent for the surface of a compressor liquid storage tank according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: using the compressor liquid storage tank surface anti-rust treatment agent as described in any one of claims 1 to 7 to vertically spray the compressor liquid storage tank after the leak detection water inspection.

Citation Information

Patent Citations

  • Steel antirust agent

    CN101368274A

  • Passivation solution for stainless steel body of railway vehicle and preparation method therefor

    CN113818017A

  • Preparation method of anti-corrosion coating, coating and application of crown ether complex as anti-corrosion coating additive

    CN114621655A

  • Environment-friendly water-based antirust agent and preparation method thereof

    CN117265522A

  • Catalyst, method for preparation thereof, method for preparing carrier for this catalyst, and diesel fraction desulfurization process

    RU2313389C1